Directly measured aerobic fitness in male Maasai of Tanzania. Issue 4 (6th September 2021) - Christensen, Dirk L.; Jørgensen, Sine W.; Koch, Lars S.; Nordsborg, Nikolai B.; Sironga, Joseph; Ramaiya, Kaushik L.; Larsen, Steen; Brage, Søren; Bygbjerg, Ib C.; Maro, Venance P.; Helge, Jørn W.
Abstract: Objectives: The agro‐pastoralist Maasai of East Africa are highly physically active, but their aerobic fitness has so far only been estimated using heart rate (HR) response to submaximal exercise and not directly measured. Thus, we aimed to measure aerobic fitness directly using respiratory gas analysis in a group of Maasai, and habitual physical activity energy expenditure (PAEE) as explanatory variable. Methods: In total, 21 (10 rural, 11 semi‐urban) of 30 volunteering Tanzanian Maasai men were eligible to participate. Respiratory gas exchange was measured during a graded exercise test until exhaustion on a stationary bicycle to determine aerobic fitness. Maximal effort criteria were at least two of the following (1) leveling off, (2) respiratory exchange ratio (RER) >1.10, and (3) maximum HR within 10 bpm of age‐estimated maximum HR. Habitual PAEE was estimated using combined accelerometry and HR monitoring. Anthropometry, biochemistry, blood pressure, resting HR, and dietary intake information were collected for background information. Results: Mean age was 43.2 (range 26–60) years, and hemoglobin was higher in the rural versus semi‐urban Maasai (16.9 vs. 15.4 g/dl, p  = .02). Mean aerobic fitness (34.4 vs. 33.3 mlO2 /min/kg, p  = .79), and mean PAEE (58.5 vs. 52.9 kJ/day/kg, p  = .64) were similar in rural and semi‐urban Maasai, respectively. Conclusions: Aerobic fitness was low to moderate in male rural and semi‐urban Maasai. This may be explained by relatively low PAEE in comparison to previous objectively measured activity levels in Maasai, which indicates recent lifestyle changes.